Science fiction and political philosophy from Bacon to Black Mirror - McCranor, Timothy; Michels, Steven; Dolgoy, Erin A.; Hale, Kimberly Hurd, 1983-; Wilford, Paul; Anderson, Nicholas; Black, Jeff J. S., 1970-; Craig, Tobin L.; Picariello, Damien K.; Bagchi, Nivedita; Sottosanti, Danielle; Kapust, Daniel J., 1976-; et al. (Politics, literature, & film., 2020)
"Sometimes called the "literature of ideas," science fiction is a natural medium for normative political philosophy. Science fiction's focus on technology, space and time travel, non-human lifeforms, and parallel universes cannot help but invoke the perennial questions of political life, including the nature of a just social order and who should rule; freedom, free will, and autonomy; and the advantages and disadvantages of progress. Rather than offering a reading of a work inspired by a particular thinker or tradition, each chapter presents a careful reading of a classic or contemporary work in the genre (a novel, short story, film, or television series) to illustrate and explore the themes and concepts of political philosophy."--publisher description.